2000
DOI: 10.1266/ggs.75.343
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of rDNA on the chromosomes of Eleusine species by fluorescence in situ hybridization.

Abstract: Mapping of rDNA sites on the chromosomes of four diploid and two tetraploid species of Eleusine has provided valuable information on genome relationship between the species. Presence of 18S-5.8S-26S rDNA on the largest pair of the chromosomes, location of 5S rDNA at four sites on two pairs of chromosomes and presence of 18S-5.8S-26S and 5S rDNA at same location on one pair of chromosomes have clearly differentiated E. multiflora from rest of the species of Eleusine. The two tetraploid species, E. coracana and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…Chromosomal localizations of rDNAs are helpful for inferring genome identity (Bisht and Mukai, 2000). However, data only by FISH are insufficient to evaluate the inter-genomic relationships in the putative amphidiploid Nicotiana species.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal localizations of rDNAs are helpful for inferring genome identity (Bisht and Mukai, 2000). However, data only by FISH are insufficient to evaluate the inter-genomic relationships in the putative amphidiploid Nicotiana species.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome research has demonstrated the significant role of polyploidy and aneuploidy in the evolution of the genus (Chennaveeraiah and Hiremath 1974; Hiremath and Chennaveeraiah 1982; Hiremath and Salimath 1991; Bisht and Mukai 2000, 2001 a , b , 2002). Biochemical, nuclear and cpDNA markers have provided valuable insight into relationships, and on the origin of the crop species (Hilu et al 1978; Hilu 1988, 1995; Hilu and Johnson 1992, 1997; Werth et al 1993, 1994; Salimath et al 1995 a ; Neves et al 2005; Dida et al 2007, 2008; Liu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the enormous amount of information, there still exists considerable disagreement over the identification of the diploid ancestors of the three polyploid species and the level of speciation and evolutionary relationships among the nine species of Eleusine (Phillips 1972, 1995; Hilu and Johnson 1997; Lye 1999; Bisht and Mukai 2000, 2001 a , 2002; Devarumath et al 2005; Neves et al 2005; Liu et al 2011). Eleusine coracana (2 n = 4 x = 36) (AABB) is considered to be an allotetraploid and has been domesticated from its wild progenitor, Eleusine africana (2 n = 4 x = 36) (AABB) (Chennaveeraiah and Hiremath 1974; Hilu and deWet 1976; Hilu et al 1978; Hilu 1988, 1995; Hiremath and Salimath 1992; Werth et al 1994; Hilu and Johnson 1997; Bisht and Mukai 2000, 2001 a , b ; Devarumath et al 2005; Neves et al 2005; Dida et al 2007, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations